Fractional anisotropy shows differential reduction in frontal-subcortical fiber bundles—A longitudinal MRI study of 76 middle-aged and older adults - Vik, Alexandra; Hodneland, Erlend; Haász, Judit; Ystad, Martin; Lundervold, Astri J.; Lundervold, Arvid (Frontiers in Aging Neuroscience, 2015)
Motivated by the frontal- and white matter (WM) retrogenesis hypotheses and the as- sumptions that fronto-striatal circuits are especially vulnerable in normal aging, the goal of the present study was to identify fiber bundles connecting subcortical nuclei and frontal ar- eas and obtain site-specific information about age related fractional anisotropy (FA) changes. Multimodal magnetic resonance image acquisitions (3D T1-weighted and diffusion weighted imaging (DWI)) were obtained from healthy older adults (N=76, range 49-80 years at inclusion) at two time points, three years apart. A subset of the participants (N=24) was included at a third time-point. In addition to the frontal-subcortical fibers, the anterior callosal fiber (ACF) and the corticospinal tract (CST) was investigated by its mean FA together with tract parameterization analysis. Our results demonstrated fronto-striatal structural connec- tivity decline (reduced FA) in normal aging with substantial inter-individual differences. The tract parameterization analysis showed that the along tract FA profiles were characterized by piece-wise differential changes along their extension rather than being uniformly affected. To the best of our knowledge, this is the first longitudinal study detecting age-related changes in frontal-subcortical WM connections in normal aging.